Assessment of the efficacy of hepatitis C treatment in Hospital Universiti Sains Malaysia (HUSM) - Yusoff, Ahmad Syahidan (2019)
Background : Management of Hepatitis C virus (HCV) infection has been evolved in the last few years. Currently, the newer treatment direct acting antivirals (DAAs) promise a higher rate of efficacy to compare to previous treatment, pegylated interferon. The goal of HCV treatment is to eradicate the virus and to avoid the progression of liver fibrosis and HCV-related disease. Sustained virologic response (SVR) is the most widely used efficacy endpoint in clinical studies of hepatitis C and represents the eradication of HCV from the body. We conduct a study to compare the efficacy of Hepatitis C treatment between pegylated interferon and DAA, it effects towards liver function and its associated factors in our cohort of patient therefore, support our continuing use of DAA in the treatment of Hepatitis C virus infection in HUSM. Methodology: This is a retrospective record review done by reviewing a record of 88 patients who were either on Pegylated Interferon or on DAAs during the period of 2011 till 2018. Subjects were who achieved undetectable viral load in serum after 12 or 24 weeks after completed therapy was taken as a sustained virological response (SVR). We also evaluated the variation of ALT at baseline and 12 weeks after completed therapy. All relevant data are gathered and recorded in statistical software for analysis. Result: Between January 2011 and September 2018, 35 patients started a DAA treatment and 53 patients had completed pegylated interferon treatment. Overall proportion of SVR12 was 92% (n=32) for DAAs and 69.8%(n=37) for interferon-based treatment. Analysis of ALT showed that the level normalized in the most patients who had achieved SVR (68%). Factors such as gender, genotype, race, pre-treatment HCV RNA level and liver cirrhosis are shown not to be associated with the efficacy of treatment. Conclusion : Achievement of the high rate of SVR represents the goal for HCV treatment and has implications to reduce risk of liver disease progression and extrahepatic disease. However, further studies are needed to include more patients in order to improve power of the study. Based on the higher rate of SVR associated with DAA therapy, this should be the first choice of treatment.